THE CONCEPT OF HISTORICAL STYLING - Z.R.Aliyeva (Galaxy International Interdisciplinary Research Journal, 2022)
The relevance of the work is due to the need to study historical vocabulary in the language of a work of art and analyze historical vocabulary, apply a practical approach to the problem of transferring lexical archaisms in translation within the framework of historical text stylization.